A Motivational Mechanism Framework for Teachers' Online Informal Learning and Innovation During the COVID-19 Pandemic - Yu, Haiqin; Zhang, Jian; Zou, Ruomeng (Frontiers in Psychology, 2021)
Online informal learning(IL) spreads quickly in COVID-19 pandemic. Studies have predicted that both online and workplace IL have potential value to individual and organization development, while, the study on its link with innovation remains scarce.As an individualized learning pattern, its functioning mechanism on innovation will deepen our understanding of the relationship between learning and innovation. Self-efficacy and autonomous motivation are considered as two streams of motivational mediating mechanism to innovation. However, previous research have proceeded largely in separation from each other. Researchers highlight the need to develop a more fine-grained theory of motivation and innovation. In addressing these literature gaps, this paper takes college teachers as the sample and focuses on the motivational mediating mechanism between online informal learning and innovation. The results showed that teachers IL can positively predict innovative teaching performance. Personal teaching efficacy and autonomous motivation played as sequential mediators on the link between IL and innovative teaching performance. This study extends the IL–innovation relationship literature and enrich understanding of cognitive oriented motivation theory, which highlights one’s internal autonomous construction is the key to innovation. Theoretical and practical implications for psychological empowerment are discussed.